Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome